Development of enzymatic biodiesel from vegetable oil and quantification of fatty acid Butyl Esters - Kumar D.; Verma B. (My University, 2025)
Biodiesel was produced by enzymatic transesterification of soybean oil with isobutanol esterifying agent and Lipase (Pseudomonas cepacia) as a biocatalyst. Fourier transform infrared spectroscopy (Thermo-Nicolet mode 5700) was employed as an analytical technique for the quantification of fatty acid butyl ester content in the produced biodiesel. The spectra of produced butyl biodiesel found in the 500-4000 per cm region, along with a declaration of 4 per cm. The method developed by Zagonel was used for quantitative analysis. Results of Fourier transform infrared spectra for oil and biodiesel shows a strong band at about 1739.4 cm-1 is because of the deformation(stretching) of ester C=O axial, two medium bands at 1002.9 and 1039.3 cm-1 related to the C-O bond stretching and a small band at 963.4 cm-1 related to C-C stretching. The strong band at about 1739.4 cm-1 was increased with time and that is recognized to the quantity of glycerol substitution present in fatty acid by butoxy radicals (butanolysis). The soybean oil strong band peak is at 1743.6 cm-1 and soybean butyl diesel strong band peak is at 1739.4 cm-1 shifting peaks indicates the transesterification. The peak of transmittance for biodiesel was different from the respective peak of soybean oil. The highest value of absorbance band at wave number 1739.4 cm-1 was used for the calculation of the concentration of ester present in the butyl biodiesel layer. © RASĀYAN. All rights reserved.